Child neglect : practice issues for health and social care - Taylor, Julie, 1961-; Daniel, Brigid, 1959- (Best practice in working with children series., 2005)
Neglect is now recognized as leading to significantly poor outcomes for children in the short and long term. It is a matter of concern for all professionals who work with children. Children who are neglected are not likely to seek help in their own right and are highly dependent on professionals such as health visitors and schoolteachers identifying and responding to their needs for support and protection. In order to carry out the key tasks of prevention, recognition and response to neglect, practitioners require up-to-date evidence-based information about the aetiology and signs of neglect a.